2011
DOI: 10.1182/blood-2011-03-344739
|View full text |Cite
|
Sign up to set email alerts
|

Erg is required for self-renewal of hematopoietic stem cells during stress hematopoiesis in mice

Abstract: Hematopoietic stem cells (HSCs) are rare residents of the bone marrow responsible for the lifelong production of blood cells. Regulation of the balance between HSC self-renewal and differentiation is central to hematopoiesis, allowing precisely regulated generation of mature blood cells at steady state and expanded production at times of rapid need, as well as maintaining ongoing stem cell capacity. Erg, a member of the Ets family of transcription factors, is deregulated in cancers; and although Erg is known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 45 publications
(69 reference statements)
6
39
0
Order By: Relevance
“…Although ERG autoinhibition has been biochemically characterized in a recent study (29), our current report presents structures of ERG and characterization of the molecular mechanism of autoinhibition. The changes in ERG activity we identified here, ∼fivefold weaker binding in ERGi and threefold weaker binding in full-length ERG, are highly relevant in a biological context, because a change in ERG expression of as little as 50% is sufficient to alter angiogenesis (13), myeloproliferation (8), and maintenance of the hematopoietic stem cell population (7,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ERG autoinhibition has been biochemically characterized in a recent study (29), our current report presents structures of ERG and characterization of the molecular mechanism of autoinhibition. The changes in ERG activity we identified here, ∼fivefold weaker binding in ERGi and threefold weaker binding in full-length ERG, are highly relevant in a biological context, because a change in ERG expression of as little as 50% is sufficient to alter angiogenesis (13), myeloproliferation (8), and maintenance of the hematopoietic stem cell population (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…ERG in particular is critical for maintenance of the hematopoietic stem cell (HSC) population. In a mouse model, the HSC population cannot recover after being challenged by sublethal radiation in heterozygous ERG animals, whereas the loss of both functional copies of ERG is embryonic lethal (7). Overexpression of the ERG gene product, located on chromosome 21, has also been implicated in the myeloproliferative disorders frequently seen in Down Syndrome patients (8), has been shown to have a dedifferentiating effect (9), and confers greater invasiveness to cell lines (10,11).…”
mentioning
confidence: 99%
“…ETS proteins are a family of over 20 helix-loop-helix domain transcription factors with diverse biological roles, including important functions in hematopoiesis and leukemia. In normal hematopoiesis, Erg is required for hematopoietic stem cell self-renewal during times of high hematopoietic stem cell cycling (11)(12)(13). Whereas the ERG locus has been studied extensively in prostate cancer, in which translocation of ERG to the TMPRSS2 locus and expression of a TMPRSS2-ERG fusion oncoprotein occurs in the majority of cases (8), ERG is also known to be translocated to the fused in sarcoma/translocated in liposarcoma (FUS/TLS) locus in rare cases of acute myeloid leukemia (AML).…”
Section: Discussionmentioning
confidence: 99%
“…Erg Mld2/+ mice (i.e., heterozygous carriers of the mutant Erg allele) had slightly reduced numbers of immunophenotypical HSCs that appeared functionally compromised in transplantation experiments. In addition, follow-up work demonstrated that although Erg haploinsufficiency was compatible with lifelong HSC self-renewal, it strongly impaired stress hematopoiesis following exposure to myelotoxic treatment (Ng et al 2011). Collectively, these data suggest that ERG could be particularly important during the expansion of HSCs.…”
mentioning
confidence: 88%
“…The E-twenty-six (ETS)-related gene (ERG) is a member of the ETS family of transcription factors, of which several, including PU.1, have been shown to play a role in HSC maintenance (Loughran et al 2008;Ng et al 2011). Erg was identified in a sensitized genetic screen as a gene involved in HSC function, and the molecular defect was assigned to a point mutation in the DNA-binding domain of ERG (Loughran et al 2008).…”
mentioning
confidence: 99%